2019
DOI: 10.3389/fgene.2019.01134
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the DNA Methylation Signature of Renal Erythropoietin-Producing Cells Governs the Sensitivity to Drugs Targeting the Hypoxia-Response Pathway in Kidney Disease Progression

Abstract: Chronic kidney disease (CKD) affects more than 10% of the population worldwide and burdens citizens with heavy medical expenses in many countries. Because a vital erythroid growth factor, erythropoietin (EPO), is secreted from renal interstitial fibroblasts [renal EPO-producing (REP) cells], anemia arises as a major complication of CKD. We determined that hypoxia-inducible factor 2α (HIF2α), which is inactivated by HIF-prolyl hydroxylase domain-containing proteins (PHDs) in an oxygen-dependent manner, tightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 74 publications
1
22
1
Order By: Relevance
“…This protocol for the isolation of fibroblasts from healthy kidneys is applicable to the isolation of myofibroblasts from fibrotic kidneys, which originate from REP cells in injured kidneys ( Souma et al., 2013 ; Sato et al., 2019a , 2019b ). Because myofibroblasts occupy a large portion of fibrotic kidneys in mice subjected to unilateral ureteral obstruction, sufficient numbers of myofibroblasts are isolated from the mice for molecular and cellular analyses ( Souma et al., 2013 ).…”
Section: Expected Outcomesmentioning
confidence: 99%
“…This protocol for the isolation of fibroblasts from healthy kidneys is applicable to the isolation of myofibroblasts from fibrotic kidneys, which originate from REP cells in injured kidneys ( Souma et al., 2013 ; Sato et al., 2019a , 2019b ). Because myofibroblasts occupy a large portion of fibrotic kidneys in mice subjected to unilateral ureteral obstruction, sufficient numbers of myofibroblasts are isolated from the mice for molecular and cellular analyses ( Souma et al., 2013 ).…”
Section: Expected Outcomesmentioning
confidence: 99%
“…EPO production is stimulated by hypoxia and regulated by hypoxia-inducible factors (HIFs). In normoxic conditions, HIFs are hydroxylated by HIF-prolyl hydroxylase domain-containing proteins (PHDs), and hydroxylated HIFs are degraded by the ubiquitin-proteasome system [36,37]. In hypoxic conditions, the hydroxylation and degradation of HIFs is inhibited, resulting in the transcriptional activation of HIF-inducible genes, including EPO.…”
Section: Two Common Ckd Complications Renal Anemia and Peritubular Capillary Loss Are Also Caused By Dysfunction Of Renal Fibroblasts/permentioning
confidence: 99%
“…HIF-1α and HIF-2α may play different roles in various anemia conditions; HIF-2α, for example, mediates nucleosome disassembly, in the mechanism of hypoxia-dependent erythropoietin induction. Animal studies have clarified that, when oxygen is available, HIF is inactivated by post biosynthetic modifications of basic amino acid residues in the α subunits [17], an oxygen-dependent function which is accomplished by proteins containing a HIF-prolyl hydroxylase domain (PHDs) [7]. Sato and coworkers recently showed that, in CKD related anemia, there is a disruption of the mechanism linking hypoxia with the consequent EPO induction.…”
Section: Anemia and Erythropoietin In Ckdmentioning
confidence: 99%
“…This is due to (I) metaplasia of renal EPO producing cells (REPs) into myofibroblasts (MF-REPs); (II) the pathological hyperactivation of PHDs as the result of kidney damage [7]. Although PHD inhibitors (e.g., roxaduxat) have been considered in the treatment of CKD-related anemia, their action may be partly neutralized, however, as CKD progression proceeds, since the HIF-2α and EPO encoding gene promoter regions are hypermethylated and therefore epigenetically silenced in MF-REPs, thus hampering the expression of these genes [7]. This is indeed a field of active research for personalized treatment applications in CKD patients, provided that a robust assessment of disease stage is accomplished.…”
Section: Anemia and Erythropoietin In Ckdmentioning
confidence: 99%
See 1 more Smart Citation